Fixed asset management: analysis of the policies and procedures of a client of Rahman Rahman Huq, chartered accountants (KPMG Bangladesh) - Niha, Sabrina Qureashi (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.